2020
DOI: 10.1017/s1368980019003604
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia, iron deficiency, iron-deficiency anaemia and their associations with obesity among schoolchildren in Guangzhou, China

Abstract: Objective:The association of Fe metabolism with obesity in children remains unclear. The present study aimed to assess the status of Fe metabolism parameters, the prevalence of anaemia, Fe deficiency (ID) and Fe-deficiency anaemia (IDA), and the associations of these variables with obesity in Chinese schoolchildren.Design:A cross-sectional study conducted in 5295 schoolchildren aged 7–11 years in Guangzhou, China, 2014–2015. Full data of anthropometric and Fe metabolic parameters were collected to assess obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…Moreover, a recent study including school-aged children from Guangzhou, China, found that obesity was associated with a lower risk of anaemia (adjusted OR = 0⋅553; 95 % CI 0⋅316, 0⋅968; P = 0⋅038) and a higher risk of Fe deficiency without anaemia (ID) (adjusted OR = 1⋅808; 95 % CI 1⋅146, 2⋅853; P = 0⋅011). However, in this work, obesity was not associated with IDA (16) . The underlying mechanisms for the abovementioned associations remain unclear.…”
Section: Introductioncontrasting
confidence: 68%
“…Moreover, a recent study including school-aged children from Guangzhou, China, found that obesity was associated with a lower risk of anaemia (adjusted OR = 0⋅553; 95 % CI 0⋅316, 0⋅968; P = 0⋅038) and a higher risk of Fe deficiency without anaemia (ID) (adjusted OR = 1⋅808; 95 % CI 1⋅146, 2⋅853; P = 0⋅011). However, in this work, obesity was not associated with IDA (16) . The underlying mechanisms for the abovementioned associations remain unclear.…”
Section: Introductioncontrasting
confidence: 68%
“…Similar results were found in a cross-sectional Canadian study on 1607 children, aged 1-3 years, which concluded that the z-score of BMI was rose inversely proportional to ferritin levels and it was associated with a higher risk of iron deficiency (22). Another study, from China that included over 5000 patients 7-11 years old observed that obesity increased the risk of ID, even though it did not apparently amplify the risk of anemia (23).…”
Section: Discussionsupporting
confidence: 78%
“…Although the difference between anemia prevalence was not significant across BMI groups among women in Peru, a decreasing trend of anemia in women was also observed with increasing BMI [ 45 ]. A high-calorie diet and adequate intake of animal-based food may increase hemoglobin formation in women with obesity [ 46 ]. A previous study with school children in China reported that although children with obesity had high hemoglobin levels, they could experience iron deficiency, which was not analyzed in our study [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high-calorie diet and adequate intake of animal-based food may increase hemoglobin formation in women with obesity [ 46 ]. A previous study with school children in China reported that although children with obesity had high hemoglobin levels, they could experience iron deficiency, which was not analyzed in our study [ 46 ].…”
Section: Discussionmentioning
confidence: 99%